Empowerment Group of Women Farmers in The Abon Making Business With The Basic Materials From The Heart of Banana in Village Dompyong Bendungan Sub District Trenggalek District - Tukiman; Ertien Rining; Andre Yusuf Trisna (Future Science)
Rural communities as poor people have complex problems, namely the factor of being economically poor, socially marginalized, and forgotten in function and dignity. Furthermore the education factor where the level of education of rural communities is still largely low. Education is important because with empowerment, the community will increase their personal and group capacities. One of the rural communities in Trenggalek district is a group of women farmers (KWT) in the village of Dompyong. In an effort to increase the income of farming families, among others, is the participation of farmer women groups in seeking additional income, both in the activities of making cassava chips and banana chips, banana floss in this village has the potential to be developed, but due to limited human resource capabilities (lack of power ) especially concerning knowledge of increasing production and marketing, the home industry of banana heart floss in Dompyong Trenggalek village has not been maximized and cannot be processed properly. Even though Health benefits for our body is to prevent the risk of stroke, prevent cholesterol, can nourish the stomach, and can be consumed for diabetics and many more benefits that are owned by the heart of this banana.The purpose of this dedication activity is to provide knowledge and insights to partners about making good and true banana heart floss and taste buds, and provide insights on marketing management so that an appropriate marketing network development model can be obtained. Whereas the target of this community service activity is the empowerment of women farmer groups (KWT) in the development of the banana heart floss business as an additional source of income for the family of women farmer groups (KWT) in Dompyong Village, Bendungan District, so that more comprehensive knowledge can be achieved on how to process abon production banana heart floss includes effective and correct marketing methods.